Tele-Pharmacists’ Prospects in Pandemic Situations: A Bangladesh Scenario - Kader Mohiuddin Abdul (International Journal of Coronaviruses, 2020)
Telemedicine and telehealth technologies are especially effective during epidemic outbreaks, when health authorities recommend implementing social distance systems. Currently, coronavirus COVID-19 has affected 210 countries around the world, killed more than 200,000 and infected more than 3 million, according to worldometer, April 26, 2020. Home-care is especially important in these situations because hospitals are not seemingly safe during pandemic outbreaks. Also, the chance to get out of the home during the lockdown period is limited. Telephone-based measures improve efficiency by linking appropriate information and feedback. It can also help provide education at distance on various health issues and topics. In addition to increasing access to healthcare, telemedicine is a fruitful and proactive way to provide a variety of benefits to patients seeking healthcare; diagnose and monitor critical and chronic health conditions; improve healthcare quality and reduce costs. The article reveals scope of pharmacy professionals in telemedicine sector during epidemic outbreaks.
Keywords: pharmacy